2008
DOI: 10.1016/j.jjcc.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Increased carotid artery plaque score is an independent predictor of the presence and severity of coronary artery disease

Abstract: Assessment of PS by carotid ultrasonography together with other risk factor assessment was clinically relevant to predict the presence and severity of CAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 25 publications
3
36
0
10
Order By: Relevance
“…2) Thus, CPS has also been used for the risk assessment for cardiovascular events. 10) PWV is an indicator of both arterial stiffness and atherosclerosis. Brachial-ankle PWV (baPWV) measurement, which uses pressure cuffs wrapped round the brachium and ankle, has become the most widely used PWV index, and has been demonstrated to be a reliable predictor of cardiovascular risk in high risk patients.…”
mentioning
confidence: 99%
“…2) Thus, CPS has also been used for the risk assessment for cardiovascular events. 10) PWV is an indicator of both arterial stiffness and atherosclerosis. Brachial-ankle PWV (baPWV) measurement, which uses pressure cuffs wrapped round the brachium and ankle, has become the most widely used PWV index, and has been demonstrated to be a reliable predictor of cardiovascular risk in high risk patients.…”
mentioning
confidence: 99%
“…Morito et al [16] found that PS more closely represented the atherosclerotic status of the carotid artery than the IMT. They also found that subjects with carotid plaques in their study group had a higher risk of heart attack as compared to those with IMT.…”
Section: Discussionmentioning
confidence: 99%
“…Согласно одномоментному исследова-нию Morito N, et al (2008) увеличение суммарной высоты бляшек на 1,0 мм коррелирует с увеличением риска наличия коронарного атеросклероза на 36% [34]. В исследовании Ikeda N, et al (2012) только сум-марная высота бляшек в отличие от ТИМ коррелиро-вала с умеренным (23-32) и выраженным (33 и более) поражением коронарного русла по шкале SYNTAX при коррекции на основные факторы риска, при этом чувствительность метода составила 96,1% при суммар-ной высоте бляшек >5 мм [35].…”
Section: Ultrasound Markers Of Premanifest Atherosclerosis Of Carotidunclassified